Splicing regulation and dysregulation of cholinergic genes expressed at the neuromuscular junction. (21st March 2017) - Ohno, Kinji; Rahman, Mohammad Alinoor; Nazim, Mohammad; Nasrin, Farhana; Lin, Yingni; Takeda, Jun‐ichi; Masuda, Akio
Abstract: We humans have evolved by acquiring diversity of alternative RNA metabolisms including alternative means of splicing and transcribing non‐coding genes, and not by acquiring new coding genes. Tissue‐specific and developmental stage‐specific alternative RNA splicing is achieved by tightly regulated spatiotemporal regulation of expressions and activations of RNA‐binding proteins that recognize their cognate splicing cis ‐elements on nascent RNA transcripts. Genes expressed at the neuromuscular junction are also alternatively spliced. In addition, germline mutations provoke aberrant splicing by compromising binding of RNA‐binding proteins, and cause congenital myasthenic syndromes (CMS). We present physiological splicing mechanisms of genes for agrin ( AGRN ), acetylcholinesterase ( ACHE ), MuSK ( MUSK ), acetylcholine receptor (AChR) α1 subunit ( CHRNA1 ), and collagen Q ( COLQ ) in human, and their aberration in diseases. Splicing isoforms of AChET, AChEH, and AChER are generated by hnRNP H/F. Skipping of MUSK exon 10 makes a Wnt‐insensitive MuSK isoform, which is unique to human. Skipping of exon 10 is achieved by coordinated binding of hnRNP C, YB‐1, and hnRNP L to exon 10. Exon P3A of CHRNA1 is alternatively included to generate a non‐functional AChR α1 subunit in human. Molecular dissection of splicing mutations in patients with CMS reveals that exon P3A is alternatively skipped by hnRNP H, polypyrimidine tract‐binding protein 1, and hnRNP L. Similarly, analysis of an exonic mutation in COLQ exon 16 in a CMS patient discloses that constitutive splicing of exon 16 requires binding of serine arginine‐rich splicing factor 1. Intronic and exonic splicing mutations in CMS enable us to dissect molecular mechanisms underlying alternative and constitutive splicing of genes expressed at the neuromuscular junction. This is an article for the special issue XVth International Symposium on Cholinergic Mechanisms . Abstract : Alternative splicing is regulated by tissue‐specific and developmental stage‐specific expression and activation of RNA‐binding proteins. Mutations affecting the splicing cis ‐element compromise finely tuned splicing mechanisms. We present physiological splicing mechanisms of genes for agrin ( AGRN ), acetylcholinesterase ( ACHE ), and MuSK ( MUSK ). We also show splicing mechanisms of the acetylcholine receptor (AChR) α1 subunit ( CHRNA1 ) and collagen Q ( COLQ ), and their aberration in congenital myasthenic syndromes. This is an article for the special issue XVth International Symposium on Cholinergic Mechanisms .